Impact on mothers of children with disabilities - Hernández Martínez, Laura; Prieto Silva, Patricia; Muñoz Domínguez, Miguel Omar; Hernández Martínez, Laura; Prieto Silva, Patricia; Muñoz Domínguez, Miguel Omar; Hernández Martínez, Laura; Prieto Silva, Patricia; Muñoz Domínguez, Miguel Omar (Corporación Universitaria Americana, 2020)
Having a child is an event that can represent many things: continuity, support for old age, company, among others. That child is expected to grow, develop, and one day be on his own. The importance of the mother in the first years of life will be fundamental. However, when this child has a disability, all this will be truncated, modifying the way of childbearing. Mothers fantasize about a child with normal characteristics and that image often never corresponds to reality. This disabled son will mobilize in the mothers their ghosts and fantasies about what they did wrong. This research shows 9 cases of mothers who had children with disabilities, congenital, acquired at the time of delivery and by accident and analyzes the repercussions that this event brought to the lives of mothers.